Comparison of Outcomes of Topical Anesthesia with Peribulbar Anesthesia in Vitrectomy for Unresolving Vitreous Hemorrhage - Muhammad Munir; Hussain Ahmaed Khaqan; Fahd Kamal Akhtar; Usman Imtiaz; Abdul Basit; Raheela Naz; Mehreen Afzal (Gandhara University, 2022)
OBJECTIVES: To compare the Surgeon's ease level and duration of surgery in topical anesthesia with peribulbar anesthesia for vitrectomy without sedation in patients with unresolving vitreous hemorrhage of duration greater than 3 months. METHODOLOGY: A randomized controlled trial was carried out at the Department of Ophthalmology, Lahore General Hospital, Postgraduate Medical Institute, Lahore from October 2017 to September 2018. A total of 110 patients were equally divided (n=55) in group A (topical anesthesia) and group B (peribulbar anesthesia) by lottery method. In group A, 0.5% proparacaine hydrochloride eye drops were instilled into the conjunctival sac every 3 minutes preoperatively 5 times before surgery. For group B patients, 5cc injection consisting of 2.5ml of 0.5% bupivacaine and 2.5ml of 1% lidocaine was injected thirty minutes before surgery. Surgical time was noted from first incision to enter the eye for vitrectomy till application of last closing suture. Surgeon ease was recorded with a 4 Grade scale. All data was recorded, entered, and analyzed by SPSS version 25.0. Continuous variables were presented as mean, standard deviation and independent t-test was applied. RESULTS:  The mean age of the patient was 43.83±9.76 years. Male cases were 78 (70.9%) and female cases were 32 (29.1%). Mean duration of surgery was 30.32±7.07 minutes and the surgeon's ease was 2.30±0.98. There was a significant difference (P<0.05) with respect to mean duration of surgery and surgeon's ease level in patients who were given topical anesthesia (28.12±6.57 minutes and 3.11±0.90) versus peribulbar anesthesia (32.52±6.92 minutes and 2.67±0.90). CONCLUSION: Topical anesthesia without sedation is better than peribulbar anesthesia for vitrectomy without sedation in patients with unresolving vitreous hemorrhage of duration greater than 3 months.